Mechanical Properties of the Shear Failure of Rock Masses with Prefabricated Sinusoidal Fractures - Limei Tian; Hongzhou Zhang; Wei Hong; Yunxia Zhang; Jinghua Zhang; Wenhui Tan (Advances in Civil Engineering)
A large number of sinusoidal fractures exist in the open-pit slopes of mines, and the mechanical properties of shear failure are of great significance to the stability of the open-pit slope. Sandstone specimens containing sinusoidal fractures with different undulated heights were prefabricated by the CNC sand-wire-electrode cutting technology to explore the effect of sinusoidal fractures on the mechanical properties of shear failure of rock masses. The TFD-20H/50J rock shear testing machine was used for shear tests on sinusoidal-fracture sandstone with different undulated heights. In the shear loading process, the prefabricated-fracture sandstone specimens with different undulated heights have the fracture-compacting stage, linear-elastic changing stage, bottom-up stage, and residual strength stage. Before peak strength, the sinusoidal prefabricated-fracture rock masses with different undulated heights have the precursory characteristics of decreased stress, which can provide an early warning for the instability and failure of rock masses. The undulated height of sinusoidal fractures significantly affects the fracture initiation and propagation of specimens. Fractures occur and develop from the prefabricated fractures at low undulated height (≤10 mm) to multiple ways under the high undulated height (>10 mm); that is, fractures occur at the prefabricated fractures and the end of specimens simultaneously. With the increased undulated height, the fractures expand from parallel to the slope of the prefabricated fractures to perpendicular to the prefabricated fractures. The fracture propagation direction of sinusoidal-fracture rock masses with different undulated heights is mainly from the middle of the slope surface of prefabricated fractures to the end. It is the main direction of the shear failure of sinusoidal prefabricated fractures, and the monitoring of weak planes should be strengthened in the actual slope engineering.